Clinicopathological finding and prognosis in bilateral breast cancer: Nakhonphanom hospital - Hunpayon, Natawan; Nakphook, Sutthichai (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2025)
Background and objectives: The incidence of bilateral breast cancer is 2-12% of patients with breast cancer. This study aimed to study and compare cliniopathological finding, associated factor, previous treatment and prognosis of patients with bilateral breast cancer, both of synchronous and metachronous bilateral breast cancer (SBBC and MBBC) who visited Nakhonphanom hospital. Material and methods: This study was a single center, retrospective descriptive study. Data was collected from medical records. 32 patients with bilateral breast cancer. (24 MBBC and 8 SBBC) who visited at Nakhonphanom hospital between 1st October 2014 – 30thSeptember 2024 were selected from the database. A total of 196 patients with unilateral breast cancer were selected as the control group. Data was analyzed by statistical distribution, frequency, mean and standard deviation (SD). The continuous data was tested for normal distribution. Quantitative variables were compared mean among two groups by Independent t-test and compared the mean more than two groups using one-way ANOVA test. Nominal categorical data was compared proportion using Fisher’s exact test. The statistically significant variance was p-value < 0.05. Result: The incidence of bilateral breast cancer in Nakhonphanom hospital is 4.15%. Diagnosis breast cancer at premenopausal period is associated risk of bilateral breast cancer, significantly (p=0.003), especially SBBC. (p=0.008) ER negative and PR negative of the first cancer are associated factors of bilateral breast cancer, significantly. (p<0.001, p=0.047) The interval between diagnosis the first and the second cancer in MBBC ranged 7-216 months. Patients who were lost to follow up had poor prognosis. Conclusion: Associated factors of bilateral breast cancer are diagnosis breast cancer in premenopausal period and ER/PR negative. Breast cancer patients should be followed up and surveillance to prevent and aware breast cancer in contra lateral breast.